Dynamic modelling of hand grasping and wrist exoskeleton: an EMG-based approach - Karis, Mohd Safirin; Kasdirin, Hyreil Anuar; Abas, Norafizah; Zainudin, Muhammad Noorazlan Shah; Muhammad, Sufri; Mior Fadzil, Mior Muhammad Nazmi Firdaus (The Science and Information Organization, 2023)
Human motion intention plays an important role in designing an exoskeleton hand wrist control for post-stroke survivors especially for hand grasping movement. The challenges occurred as sEMG signal frequently being affected by noises from its surroundings. To overcome these issues, this paper aims to establish the relationship between sEMG signal with wrist angle and handgrip force. ANN and ANFIS were two approaches that have been used to design dynamic modelling for hand grasping of wrist movement at different MVC levels. Input sEMG signals value from FDS and EDC muscles were used to predict the hand grip force as a representation of output signal. From the experimental results, sEMG MVC signal level was directly proportional to the hand grip force production while hand grip force signal values will depend on the position of wrist angle. Its also concluded that the hand grip force signal production is higher while the wrist at flexion position compared to extension. A strong relationship between sEMG signal and wrist angle improved the estimation of hand grip force result thus improved the myoelectronic control device for exoskeleton hand. Moreover, ANN managed to improve the estimation accuracy result provided by ANFIS by 0.22 summation of integral absolute error value with similar testing dataset from the experiment.